Integrating Operations and Marketing Perspectives of Product Innovation: The Influence of Organizational Process Factors and Capabilities on Development Performance - Tatikonda, Mohan V.; Montoya-Weiss, Mitzi M. (Management Science, 2001)
This paper adopts a multidisciplinary view of innovation by integrating operations and marketing perspectives of product development. The conceptual framework builds on the resource-based view of the firm and organizational information-processing theory to characterize relationships among organizational process factors, product development capabilities, critical uncertainties, and operational/market performance in product development projects. Data from a cross-sectional sample of 120 completed development projects for assembled goods is analyzed via a two-stage hierarchical moderated regression approach. The findings show that: (1) the organizational process factors studied are associated with achievement of operational outcome targets for product quality, unit cost, and time-to-market; (2) achievement of operational outcomes aids the achievement of market outcomes, in turn suggesting that development capabilities are indeed valuable firm resources; and (3) these relationships are robust under conditions of technological, market, and environmental uncertainty. This article provides practical insight into how product development projects can be better managed for operational and market success. Additionally, this article sets a theoretical and empirical basis for future research on the influence of organizational process factors and capabilities on diverse product-innovation outcomes.